PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE ROUND ROBIN TERHADAP KEMAMPUAN PUBLIC SPEAKING SISWA KELAS VII DI SMPN 1 MAKALE SELATAN, KABUPATEN TANA TORAJA - Maharani; Muh.Said; Sakmawati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This research aims to 1) Understand the description of the application of the Round Robin type cooperative learning model at SMPN 1 Makale Selatan, 2) Understand the description of the public speaking abilities of class VII students after implementing the Round Robin type cooperative learning model and 3) Understand the influence of the Round Robin type cooperative learning model on public speaking abilities. The research used a quantitative experimental method with a Nonequivalent Control Group Design involving 60 students divided into experimental classes and control classes. The research results show that 1) The implementation of the Round Robin type The research results show that 1) The implementation of the Round Robin type cooperative learning model is effective, demonstrated by the students' ability to wait their turn to speak, convey ideas in turns, listen to each other and the active involvement of all group members so that learning participation is even. 2) Class VII students' public speaking abilities increased significantly in the experimental class with an average post-test score of 76.63. This increase is reflected in indicators of public speaking ability, namely speaking fluency, accuracy in word choice, understanding of content/themes, flow of delivery, intonation and eye contact. 3) The application of the Round Robin type cooperative learning model has a significant influence on students' public speaking abilities as proven through the independent sample t-Test with a significance value of 0.003.